Dynamics of colonization and expression of pathogenicity related genes in fusarium oxysporum f.sp ciceri during chickpea vascular wilt disease progression - Upasani, Medha L.; Gurjar, Gayatri S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Plos One, 2016)
Fusarium wilt caused by Fusarium oxysporum f.sp. ciceri (Foc) is a constant threat to chickpea productivity in several parts of the world. Understanding the molecular basis of chickpea-Foc interaction is necessary to improve chickpea resistance to Foc and thereby the productivity of chickpea. We transformed Foc race 2 using green fluorescent protein (GFP) gene and used it to characterize pathogen progression and colonization in wilt-susceptible (JG62) and wilt-resistant (Digvijay) chickpea cultivars using confocal microscopy. We also employed quantitative PCR (qPCR) to estimate the pathogen load and progression across various tissues of both the chickpea cultivars during the course of the disease. Additionally, the expression of several candidate pathogen virulence genes was analyzed using quantitative reverse transcriptase PCR (qRT-PCR), which showed their characteristic expression in wilt-susceptible and resistant chickpea cultivars. Our results suggest that the pathogen colonizes the susceptible cultivar defeating its defense; however, albeit its entry in the resistant plant, further proliferation is severely restricted providing an evidence of efficient defense mechanism in the resistant chickpea cultivar.

Chickpea-fusarium oxysporum interaction transcriptome reveals differential modulation of plant defense strategies - Upasani, Medha L.; Limaye, Bhakti M.; Gurjar, Gayatri S.; Kasibhatla, Sunitha M.; Joshi, Rajendra R.; Kadoo, Narendra Y.; Gupta, Vidya S. (Scientific Reports, 2017)
Fusarium wilt is one of the major biotic stresses reducing chickpea productivity. The use of wilt-resistant cultivars is the most appropriate means to combat the disease and secure productivity. As a step towards understanding the molecular basis of wilt resistance in chickpea, we investigated the transcriptomes of wilt-susceptible and wilt-resistant cultivars under both Fusarium oxysporum f.sp. ciceri (Foc) challenged and unchallenged conditions. Transcriptome profiling using LongSAGE provided a valuable insight into the molecular interactions between chickpea and Foc, which revealed several known as well as novel genes with differential or unique expression patterns in chickpea contributing to lignification, hormonal homeostasis, plant defense signaling, ROS homeostasis, R-gene mediated defense, etc. Similarly, several Foc genes characteristically required for survival and growth of the pathogen were expressed only in the susceptible cultivar with null expression of most of these genes in the resistant cultivar. This study provides a rich resource for functional characterization of the genes involved in resistance mechanism and their use in breeding for sustainable wilt-resistance. Additionally, it provides pathogen targets facilitating the development of novel control strategies.